1993
DOI: 10.3109/00048679309072119
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder in Australian Prisoners of the Japanese: A Clinical Study

Abstract: The clinical findings of examination of 11 Australian prisoners of the Japanese (POWs (J)) are reported. They were examined for evidence, past or present, of Post-Traumatic Stress Disorder (PTSD). Three currently satisfied the DSM-III-R criteria for a diagnosis of PTSD and at least three more would probably have done so if a complete assessment had been possible. All but two described many of the symptoms of PTSD and would probably have satisfied the criteria for the diagnosis at some time following their rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Prototypical stressors of ageing, such as retirement, the loss of a spouse or close friends, health problems and an increased awareness that, once again, death is close, may all drive worsened functioning and increased reporting of PTSD symptoms 2 . Similar findings have been noted in participants who were Australian POWs in the Changi Prison camp or on the Burma Railway during World War II 6 , 7 …”
Section: Psychological and Cognitive Problemssupporting
confidence: 53%
See 1 more Smart Citation
“…Prototypical stressors of ageing, such as retirement, the loss of a spouse or close friends, health problems and an increased awareness that, once again, death is close, may all drive worsened functioning and increased reporting of PTSD symptoms 2 . Similar findings have been noted in participants who were Australian POWs in the Changi Prison camp or on the Burma Railway during World War II 6 , 7 …”
Section: Psychological and Cognitive Problemssupporting
confidence: 53%
“…Although some of the late problems experienced by Jewish Holocaust survivors are unique, others are common to other groups who have survived severe physical and psychological trauma such as Australian prisoners of war (POWs) on the Burma Railway or in the Changi Prison camp, 6 , 7 and more recent waves of immigrants to Australia from, for example, Vietnam, Cambodia, Bosnia and Sudan 8…”
mentioning
confidence: 99%
“…To summarize, predictors of PTSD in wartime include level of exposure to com bat (Green & Berlin, 1987;Foy & Card, 1987), violence (Stretch et al, 1985), and ethnic cleansing (Weine, Becker, McGlash an, Laub et al, 1995;Weine, Becker, Mc Glashan, Vojvoda et al, 1995), proximity to traumatized individuals (Durham, Mc Cammon, & Allison, 1985), subjective im pact of the trauma (Gre�n & Berlin, 1987;Sivik et al, 1997), and negative social sup port structures after war (Norman, 1988). It has also been found that PTSD symptoma tology can persist for years after a war is over (Watson, 1993). (Stretch et al, 1985), it was hypothesized that general exposure to the war would best predict symptoms of This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
mentioning
confidence: 99%
“…The situations faced by physicians, psychologists, and psychiatrists on a daily basis in war and postwar environments may be considered independent traumatic stressors. PTS symp tomatology arising from such exposure may last for years(Watson, 1993) and affect job performance, with consequent implica tions for the treatment of others. Future re search is clearly needed for more extensive investigation of the level of PTS in health care professionals, and should extend to hospitals throughout the country and the region.…”
mentioning
confidence: 99%
See 1 more Smart Citation